Identifying constraints and limits to climate change adaptation in Austria under deep uncertainty - Schinko, Thomas; Karabaczek, Veronica; Menk, Linda; Kienberger, Stefan (Frontiers in Climate, 2024)
Although humanity has always been adapting to a changing environment, the accelerated rate of climate change in combination with continued socioeconomic development and the delay in climate action result in deep uncertainties, further challenging policy and decision making. A main are of concern, triggered by the increasing frequency and intensity of climatic hazards are growing uncertainties regarding the effectiveness of prevailing adaptation strategies, as well as constraints and eventually limits to adaptation. The existing literature is largely conceptual and focusses on the Global South, where evidence for reaching adaptation limits already exists. In this study, we aim to uncover whether Austria, a Global North country, faces intolerable risks from climate change and experiences adaptation constraints that may trigger limits to adaptation. As there are still considerable uncertainties involved in quantifying potential adaptation limits, we use a social science approach to collect first empirical evidence on this crucial issue. We identify and discuss sources of concern based on semi-structured interviews (n=26) with climate change adaptation and disaster risk management experts. Our results indicate that although Austria may currently not face physical constraints, which could lead to “hard” adaptation limits, it is nevertheless essential to upgrade existing adaptation strategies for more severe climatic events that may impose “soft” adaptation limits at the local and individual level. Many of these perceived soft adaptation limits are linked to constraints in imagination, awareness, and knowledge, but also to confining decision-making processes and the locked-in focus on technical adaptation measures, which cannot be scaled up indefinitely. To overcome these constraints and avoid adaptation limits, we suggest more inclusive stakeholder involvement in adaptive planning and the design of climate strategies by fostering bottom-up or participatory processes and integrating disaster risk management and climate change adaptation more strongly within polycentric risk governance approaches. Our insights can be seen as a precursory scoping study for the establishment of comprehensive decision making under deep uncertainty approaches in Austria and beyond, since at least many Global North countries share similar constraints and uncertainties regarding technological, economic, and political trends.